Factores de riesgo y calidad de vida de pacientes con insuficiencia venosa crónica de la clínica Abendaño de Loja - Granda Elizalde, Judith Marisol (2022)
Chronic venous insufficiency is the most common vascular and hereditary disease that affects particularly to the venous system of the lower members, impacting directly in the quality of life of who suffers from it. The Present research had the purpose of knowing the modifiable and non-modifiable risk factors of patients with insufficiency venous chronicle disease of the Clinic Abendaño from Loja, the level of deterioration of the quality of life according to sex and group of age, and to correlate bothvariables. A quantitative, prospective, cross-sectional cohort approach was applied, with a sample of 70 participants, conformed by 75.7% women Y 24.3% males who met the inclusion and exclusion criteria, to whom a survey on risk factors and the CIVIQ-14 questionnaire on the repercussions of venous insufficiency chronic quality of life were applied. The predominant modifiable factors were consumption of contraceptives 41.5% (n=22), sedentary lifestyle and standing 35.7% (n=25) in mature adults; non-modifiable prevalent factors were natural aging 44.3% (n=31), background hereditary 21.4% (n=15) and multiparity 47.2% (n=25) in the same. The moderate level of deterioration prevailed in mature adults 20% (n=14). Evidenced relationship between non-modifiable risk factors and levels of impairment of quality of life, being p = 0.00007. Therefore, it is concluded that there are factors that can be modified, based on the practice of physical exercise, changes or modifications in the static position and decrease in body mass index